2023
DOI: 10.1097/j.pain.0000000000002885
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn about selective attention processes in individuals with chronic pain using reaction time tasks? A systematic review and meta-analysis

Abstract: Information-processing biases such as attentional, interpretation, and memory biases are believed to play a role in exacerbating and maintaining chronic pain (CP). Evidence suggests that individuals with CP show attentional bias toward pain-related information. However, the selective attentional processes that underpin this bias are not always well outlined in the literature. To improve current understanding, a systematic review was performed using a descriptive synthesis of reaction time-based studies. A rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…The study was pre-registered on the open science framework (OSF) (Abudoush et al 2021) at the beginning of the data collection and before any data had been checked. The Participants were told to respond as quickly as possible according to degree of the color of the target box frame (i.e., pressing "up" key for light green and "down" key for dark green) research was conducted using a hybrid approach; that is, both remote supervised sessions and face-to-face research sessions were used depending on the timing and participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was pre-registered on the open science framework (OSF) (Abudoush et al 2021) at the beginning of the data collection and before any data had been checked. The Participants were told to respond as quickly as possible according to degree of the color of the target box frame (i.e., pressing "up" key for light green and "down" key for dark green) research was conducted using a hybrid approach; that is, both remote supervised sessions and face-to-face research sessions were used depending on the timing and participant.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated according to the critical effect (i.e., the interaction of 3 predictors which are group type, cue condition, and word type) of the Posner task, which has the highest number of factors. Multiple regression model general sample equation was used by comparing sample size in other high-quality studies from a systematic review and meta-analysis conducted by the research team (i.e., 50 + 8 k) (Abudoush et al 2021). To avoid any disruption affecting the study during the COVID-19 pandemic, a twenty-five percent dropout ratio was added to the sample totalling a hundred participants (i.e., 50 for each experimental group arm ;Faul et al 2007).…”
Section: Participantsmentioning
confidence: 99%
“…Contemporary models propose that attentional processing of pain information plays a pivotal role in the development and maintenance of chronic pain ( Todd et al, 2018 ; Van Ryckeghem et al, 2019 ). In particular, it has been suggested that people who exhibit a heightened focus on pain-related information ( i.e., pain-related attention bias) tend to report amplified levels of pain and disability and have a higher likelihood for developing chronic pain see Abudoush et al (2023) and Van Ryckeghem & Crombez (2018) for an overview of theoretical accounts. Furthermore, numerous experimental studies have shown that the level of pain-related attention bias is increased in chronic pain patients compared to healthy volunteers ( Abudoush et al, 2023 ; Crombez et al, 2013 ; Todd et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been suggested that people who exhibit a heightened focus on pain-related information ( i.e., pain-related attention bias) tend to report amplified levels of pain and disability and have a higher likelihood for developing chronic pain see Abudoush et al (2023) and Van Ryckeghem & Crombez (2018) for an overview of theoretical accounts. Furthermore, numerous experimental studies have shown that the level of pain-related attention bias is increased in chronic pain patients compared to healthy volunteers ( Abudoush et al, 2023 ; Crombez et al, 2013 ; Todd et al, 2018 ). Yet, despite these findings, available studies have often failed to show that changes in pain-related attentional bias are key in improving pain outcomes ( Todd et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%